Assessing the Intrinsic Roles of Key Dopant Elements in High‐Nickel Layered Oxide Cathodes in Lithium‐Based Batteries. Issue 12 (13th February 2023) - Cui, Zehao; Guo, Zezhou; Manthiram, Arumugam
Abstract: A rational compositional design is critical for utilizing LiNiO2 ‐based cathodes with Ni contents > 90% as promising next‐generation cathode materials. Unfortunately, the lack of a fundamental understanding of the intrinsic roles of key elements, such as cobalt, manganese, and aluminum, makes the rational compositional design of high‐Ni cathodes with a limited range of dopants (<10%) particularly challenging. Here, with 5% single‐element doped cathodes, viz., LiNi0.95 Co0.05 O2, LiNi0.95 Mn0.05 O2, and LiNi0.95 Al0.05 O2, along with undoped LiNiO2 (LNO), the influences of the dopants are systematically examined through a control of cutoff charge energy density and a common practice of cutoff charge voltage. Comprehensive investigations into the electrochemical properties, combined with in‐depth analyses of the structural and interfasial stabilities and electrolyte decomposition pathways through advanced characterizations, unveil the following: i) the intrinsic role of dopants regulates the cathode energy density or state‐of‐charge and, more critically, the occurrence of H2–H3 phase transition, which essentially dictates cyclability; ii) undoped LNO can be stabilized well with the avoidance of H2–H3 phase transition; and iii) Co provides more merits overall with an optimized electrochemical operating condition. This work provides guidance for the compositional design of high‐energy‐density high‐Ni cathodes and sheds light on the challenges of removing Co. Abstract : In‐depth analyses on the electrochemical behaviors and structural and interphasial stabilities of LiNiO2, LiNi0.95 Co0.05 O2, LiNi0.95 Mn0.05 O2, and LiNi0.95 Al0.05 O2 suggest that the intrinsic roles of key dopant elements in high‐nickel cathodes are regulating energy density, degree of delithiation, and extent of H2–H3 phase transition, contrary to the common belief that dopants, especially Mn, can inherently enhance the overall stabilities of high‐nickel cathodes.